Polygraph: a palimpsest pigment factory: a colour plant as a recording device for the sedimented scars on Johannesburg's mining landscape - Vally, Sumayya (My University, 2015)
The mining that gave rise to Johannesburg as a city has left in its wake pieces of geologically disturbed, disused, and unusable land. These leftover fragments of landscape carry with them, not only memory of the city’s foundations, but scars of the mining processes that now render them unusable - Not only do these vaguescapes have potential for the memory within them to be unearthed, but they are highly polluted, and seek to be reimagined as productive city spaces. The chosen site, an abandoned piece of mineland with a concealed old mine shaft; on the edge of a highway on the fringe of the CBD, is simultaneously highly visible to the city, but forgotten to it. Its positioning is unique in that it allows for the potential for the extraction of the mine pollutants and site remediation to become a highly visible process. Understanding and uncovering layers and traces of the site as means of understanding what is possible on this highly polluted landscape became an important architectural and design generator. The architecture consolidates and reimagines the fragments of ruin, both physical and ephemeral, contained on the site, and curates the users experience through these forgotten traces. Its programme - a colour plant, which extracts useful metallic colour pigments from the contaminated earth, becomes a visceral reminder of these past traces ;and a recording device for the current consequences of past mining activity. The approach is an almost critical speculation. The age of the picturesque landscape is no more. Our effects on the land have depleted the earth and diseased its rhythms. But these unstable consequences hold possibilities that can be engaged with imaginatively; rather than merely re-mediated. How can architecture engage with this instability? The project accepts the presence of rising acid mine water; and imagines a new reality emerging from it. The project is a comment on our own epoch; one where waste, toxicity and radiation are so rife, that they are now a quiet, sinister backdrop to our world. More than an apocalyptic future, this project deals with a dystopian present. The precarious site conditions pose questions for an architecture which can engage with the instability, and not merely withstand it. The architectural concern is to render visible and intensify a consciousness of these traces, to investigate a palimpsest infrastructure. Colour, like architecture is a link between the conscious and the subconscious. It is a mediator between the realms. It holds possibilities for suggesting and molding atmospheres and perceptions. The architecture negotiates all the realms, concerned with past, present and future. It consolidates and makes apparent the traces but it is also developed with an awareness that it becomes part of these traces. It is an intervention which aims to heighten an awareness of the presence of the past in the life of the city; and also as palimpsest infrastructure; as a recording device for the geological happenings of the earth.
Keywords: Urban renewal; South Africa, Johannesburg; Gold mines and mining; Acid mine drainage